Integrating hots into language classes in the 21st century - Mat Daud, Nuraihan (Universitas Islam Sultan Agung (UNISSULA), 2017)
In order to provide high quality instruction to learners, teachers need to consider critical thinking as one of their educational goals. To develop higher order thinking skills (HOTS) more room needs to be given to students for them to analyse, evaluate and create. Yet in many language classrooms, examinations are still the dominant mode in evaluating students’ performance. This paper will discuss the teaching strategies and approaches that can be adopted in language classrooms to achieve this purpose. The various assessment procedures that can be adopted will also be discussed. The use of appropriate technological tools is also emphasized to suit the needs of the digital natives and digital immigrants. They can be used to improve student engagement in class activities and motivate them to learn. All these call for a change in the teacher’s style of teaching to accommodate the changes especially if the aim is to produce learners who are both proficient and critical.